The role of dinoflagellate bioluminescence in deterring copepod grazing - Di Bari, Davide (2025)
Dinoflagellates are the most common marine bioluminescent organisms. Light emission results from a complex mechanism, involving not only a mechanical or chemical stimulation of scintillons, but also an enzymatic reaction between luciferase and luciferin, and, in some cases, a luciferin-binding protein. This enzymatic reaction produces light emission at 474 nm. Numerous experimental studies support the hypothesis that the adaptive significance of dinoflagellate bioluminescence is a defense against predators, such as copepods. This paper aims to understand why the dinoflagellate bioluminescence deters copepod grazing, experimentally testing three primary hypotheses: startle response, aposematic warning, and burglar alarm. Different types of light sources were tested, and the number of copepods present within the illuminated area constituted a variable. Results showed significant differences between all three experimental conditions and the dark control condition. Particularly, the data supports the hypothesis that the blinking light acts as a startling or confusing factor, which may deter copepod grazing. However, light pollution presents a significant threat, as it can inhibit the bioluminescence of dinoflagellates. This inhibition could compromise the essential predator-prey balance among organisms at the base of marine food chain. Future studies on the effect of various types, intensities, and colors of intermittent or continuous light are suggested to evaluate the processes of trophic interaction in bioluminescent marine plankton.